Given: h(x):2x+4 and k(x): x²-6?

1. k(x-1)

2.h(h(x))

3. h(k(x))

4. k(h(x))

2 Answers

Relevance
  • Anonymous
    7 years ago
    Favorite Answer

    k(x) = x² - 6

    k(x - 1) = (x - 1)² - 6

    k(x - 1) = x² - 2x + 1 - 6

    k(x - 1) = x² - 2x - 5

    h(x) = 2x + 4

    h(h(x)) = 2(2x + 4) + 4

    h(h(x)) = 4x + 8 + 4

    h(h(x)) = 4x + 12

    h(x) = 2x + 4, k(x) = x² - 6

    h(k(x)) = 2(x² - 6) + 4

    h(k(x)) = x² - 12 + 4

    h(k(x)) = x² - 8

    Using the same idea as number 1, you can do number 4.

  • Anonymous
    7 years ago

    ^=power

    1. x^2-2x-5

    2. 4x+12

    3.2x^2-8

    4. 4x^2+16x+10

Still have questions? Get your answers by asking now.